2008
DOI: 10.1098/rspb.2008.0201
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the spawning grounds of North Sea cod ( Gadus morhua ) by direct and indirect means

Abstract: Despite recent evidence for sub-stock structuring, North Sea cod are assessed as a single unit. As a consequence, knowledge of sub-stock trends is poor. In particular, there are no recent evaluations of which spawning grounds are active. Here we report results from the first ichthyoplankton survey to cover the whole North Sea. Also, this survey, conducted in 2004, was the first to make extensive use of DNA-based molecular methods to unambiguously identify early developmental stage cod eggs. We compare the find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(51 citation statements)
references
References 19 publications
2
48
1
Order By: Relevance
“…Cod spawning in the North Sea occurs in the Southern Bight, German Bight, Dogger Bank and the English Channel (Fig. 1), which constitutes the southernmost edge of Atlantic cod spawning distribution (Fox et al 2008, Brander et al 2010 in the Northeast Atlantic. Spawning appears to be not equally distributed in these areas but restricted to specific regions (Daewel et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Cod spawning in the North Sea occurs in the Southern Bight, German Bight, Dogger Bank and the English Channel (Fig. 1), which constitutes the southernmost edge of Atlantic cod spawning distribution (Fox et al 2008, Brander et al 2010 in the Northeast Atlantic. Spawning appears to be not equally distributed in these areas but restricted to specific regions (Daewel et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Fox et al 2009) and adaptive structuring (Hutchings et al 2007) remain contentious. Tagging and oceanographic studies indicate a high proportion of resident non-migratory stocks (Robichaud & Rose 2004) as well as discrete spawning locations within single management units (Fox et al 2009); both observations support a hypothesis of unrecognized diversity.…”
Section: Introductionmentioning
confidence: 99%
“…Fox et al 2009) and adaptive structuring (Hutchings et al 2007) remain contentious. Tagging and oceanographic studies indicate a high proportion of resident non-migratory stocks (Robichaud & Rose 2004) as well as discrete spawning locations within single management units (Fox et al 2009); both observations support a hypothesis of unrecognized diversity. In contrast, studies of neutral microsatellite loci and mtDNA generally indicate weak spatial structuring over large spatial scales (Bentzen et al 1996;O'Leary et al 2007;Carr & Marshall 2008) consistent with a significant mismatch between the spatial scale of genetic differentiation and management (Reiss et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Tagging studies of plaice have revealed a close proximity of annual spawning locations by specific females on Dogger Bank (see Hunter et al, 2003). Similarly, a recent survey of Atlantic cod eggs suggested that spawning was restricted to a number of relatively small "pockets" of activity in the North Sea including regions of Dogger Bank and different areas within the German Bight (Fox et al, 2008). Importantly, the results of that survey suggested that the traditional spawning sites of cod are still being utilized despite poor recruitment in recent years (ICES, 2005).…”
Section: North Sea Winter and Early Spring Spawnersmentioning
confidence: 99%